2020
DOI: 10.3390/toxins12120800
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Waste Counteracts Aflatoxin B1 Toxicity in Piglet Mesenteric Lymph Nodes

Abstract: Aflatoxin B1 (AFB1) is a mycotoxin that frequently contaminates cereals and cereal byproducts. This study investigates the effect of AFB1 on the mesenteric lymph nodes (MLNs) of piglets and evaluates if a diet containing grape seed meal (GSM) can counteract the negative effect of AFB1 on inflammation and oxidative stress. Twenty-four weaned piglets were fed the following diets: Control, AFB1 group (320 μg AFB1/kg feed), GSM group (8% GSM), and AFB1 + GSM group (8% GSM + 320 μg AFB1/kg feed) for 30 days. AFB1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Among the triad of genes coding for antioxidant enzymes (superoxide dismutase, CAT and GPX), CAT expression was also influenced by AFB1. This gene is down-regulated, in agreement with other authors who described a reduced catalase activity after AF exposure on mice brain, piglet mesenteric lymph nodes and chicken duodenal tissue [87][88][89].…”
Section: Whole-transcriptomic (Rna-seq) Investigationssupporting
confidence: 92%
See 1 more Smart Citation
“…Among the triad of genes coding for antioxidant enzymes (superoxide dismutase, CAT and GPX), CAT expression was also influenced by AFB1. This gene is down-regulated, in agreement with other authors who described a reduced catalase activity after AF exposure on mice brain, piglet mesenteric lymph nodes and chicken duodenal tissue [87][88][89].…”
Section: Whole-transcriptomic (Rna-seq) Investigationssupporting
confidence: 92%
“…A number of studies proved AFB1 causes inflammation; in addition, it shows immunomodulatory effects [ 89 , 104 , 105 ]. As a consequence, our attention was caught by the altered expression of IL-5 , IL-11 , TNF , TLR-4 and TLR-2 , and the protective effect shown by BEN.…”
Section: Discussionmentioning
confidence: 99%
“…Along the same line, other authors demonstrated that the antioxidant compounds of grape seed meal counteracted AFB1 toxicity in piglet mesenteric lymph nodes, showing a reduction of AFB1-induced oxidative stress by increasing the activity of glutathione peroxidase (GPx) and superoxide dismutase (SOD) and decreasing lipid peroxidation [41]. Supplementing the diet of ducks with antioxidants such as curcumin increased antioxidant capacity, inhibiting lipid and protein oxidation in their meat [42].…”
Section: Bread Typementioning
confidence: 87%
“…For this reason, to prevent or mitigate aflatoxicosis in farmed animals, the use of feed additives, consisting of botanical extracts with known antioxidant capacities, is a viable option. For instance, the efficacy of curcumin has been widely tested [ 21 , 22 , 23 , 24 , 25 ]; besides curcumin, several natural polyphenols have also been investigated, providing encouraging results [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Among them, the use of resveratrol (R) represents a promising strategy.…”
Section: Introductionmentioning
confidence: 99%